Treatment of ALK-rearranged non-small-cell lung cancer with brigatinib as second or later lines: real-world observations from a single institution. Issue 7 (August 2019) - Hochmair, Maximilian; Weinlinger, Christoph; Schwab, Sophia; Naber, Jakob; Setinek, Ulrike; Krenbek, Dagmar; Urban, Matthias H.; Fabikan, Hannah; Watzka, Stefan; Koger, Renate; Fazekas, Andreas; Bitterlich, Erwin; et al.
Abstract : The second-generation ALK tyrosine kinase inhibitor brigatinib has recently been approved in the European Union for use after crizotinib treatment in patients with EML4–ALK -rearranged lung cancer. In the current study, brigatinib was investigated as second-line or later-line treatment in 35 patients who had developed resistance to crizotinib, ceritinib, or alectinib. Most patients (68.6%) received brigatinib as second or third line (range: second to 12th line). In the total cohort, complete and partial responses were obtained for 9.1 and 75.8%, respectively. Overall median progression-free survival was 9.9 months, whereas the largest treatment cohort (brigatinib after crizotinib failure) showed a median progression-free survival of 8.4 months. Fifty-four percent of patients with baseline brain metastases responded to brigatinib treatment. Brigatinib was highly effective after crizotinib and ceritinib failure. Six patients had received alectinib as monotherapy, second-line, or third line before brigatinib; of these, four experienced partial responses and two progressed responses. Brigatinib treatment was well tolerated.